Overview of FLORIS updates. Issue 2 (September 2020) - Fleming, Paul; King, Jennifer; Bay, Christopher J.; Simley, Eric; Mudafort, Rafael; Hamilton, Nicholas; Farrell, Alayna; Martinez-Tossas, Luis
Abstract: In this paper, we review updates made to the FLORIS (FLOw Redirection and Induction in Steady State) open-source framework for wind farm control modeling, design and analysis. The updates are focused on improvements for large arrays of turbines - including heterogenous inflows and incorporating second-order wake steering effects - design, and analysis tools for practical application of wind farm control, and improvements to the software architecture for best practices in modularization and cooperative development.